Surgical Management of Recurrent Thymic Epithelial Tumors. Issue 1 (January 2015) - Mizuno, Tetsuya; Okumura, Meinoshin; Asamura, Hisao; Yoshida, Kazuo; Niwa, Hiroshi; Kondo, Kazuya; Horio, Hirotoshi; Matsumura, Akihide; Yokoi, Kohei
<x xml:space="preserve">Abstract</x> Background: There is no standard treatment for recurrent thymic epithelial tumors. Although the efficacy has not been validated based on the large series studies, surgical resection is sometimes employed for patients with recurrent thymic tumors. The aim of this study is to evaluate the surgical outcomes for recurrent thymic epithelial tumors based on the Japanese nationwide database. Methods: From the database of patients whose thymic epithelial tumors were treated surgically from 1991 through 2010, the cohort who developed recurrence after the initial resection was extracted. Clinicopathological factors were reviewed, and the prognostic factors of re-resected cases were examined. Results: Twenty-eight hundred thirty-five patients who underwent surgical resection of thymic epithelial tumors were registered to the database. Among these patients, 420 (14.8%) experienced recurrence. One hundred sixty-two patients were treated surgically and 243 were treated nonsurgically for recurrent disease. The 5- and 10-year postrecurrence survival rates were 82.7% and 68.2%, respectively, in the surgery group and 43.5% and 25.4%, respectively, in the nonsurgery group (p < 0.001). According to univariate analyses, female sex and the pathological Masaoka I-II stage, nonthymic carcinoma, absence of preoperative treatment and longer recurrent-free interval (RFI) were significantly favorable factors for survival in the surgery group. According to the multivariate analysis, nonthymic carcinoma histology and longer RFI were identified to be independent prognostic factors. Conclusions: The surgical outcomes of recurrent thymic epithelial tumors are favorable in selected patients. The role of re-resection may be limited in the setting of thymic carcinoma and/or a short RFI.